Drug Utilization Pattern in Elderly Hospitalized Patients in Tertiary Care Hospitals of Quetta, Pakistan - Ali, Tayyab; Ul Haq, Noman; Razaque, Ghulam; Saood, Muhammad; Nasim, Aqeel; Shah, Yasmin; Tahir, Maria; Khan, Ramina (Journal of Pharmacy Practice and Community Medicine)
Background: Changes in Pharmacokinetics and pharmacodynamics in different age groups, especially in elderly age group, have extensively been documented and studied and concurrent chronic diseases may underlie polypharmacy in elderly. Aim: The aim of this study was to assess drug utilization pattern in elderly hospitalized patients in tertiary care hospitals of Quetta. Methods: Specifically, designed questionnaire based, cross sectional study was conducted in Bolan Medical Complex Hospital and Sandeman Provincial Hospital Quetta with total of 397 participants. Non-Probability convenience sampling technique was used in this study. Cronbach alpha test was applied to check reliability of questionnaire, Cronbach alpha value was 0.886 that is acceptable range. Results: Majority of the participants were from age group 60 to 70 years (n=301, 75.8%), fever and cough were present in majority of hospitalized patients (n=180,11.7%). Majority (n=232, 58.4%) of participants were having uncontrolled disease with yearly health service utilization of more than 3 times (n=234, 58.9), medication recommended to majority (146, 36.8%) of participants were 4. Ceftriaxone was mostly prescribed in cough (n=162,90%), hypertension (n=114, 67.1%), fever (n=154, 85.6%) of cases, while in gastritis omeprazole was mostly prescribed (n=84, 73.7%). Most of the hospitalized patients were complaint to ceftriaxone, omeprazole, dimenhydrinate and diclofenac sodium. Conclusion: Ceftriaxone was most prescribed drugs among elderly patients that were admitted in different specialty departments. Most of the elderly patients had uncontrolled disease status. This study concluded that the compliance to medication was 82.1% of elderly patients.
Keywords: Compliance; Drug Utilization; Drug utilization pattern; Elderly hospitalized patients; Quetta